Serum progesterone levels on the day of hCG trigger and ICSI outcome: a retrospective observational cohort study - Amin, Kinnari Vilaschandra; Nadkarni, Purnima; Singh, Pooja Nadkarni; Singh, Prabhakar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Whether serum progesterone (P4) level on the day of human chorionic gonadotropin (hCG) trigger is related to the outcome of artificial reproductive technology (ART) is still a debatable issue. The objective of this study was to evaluate relationship between serum Progesterone levels on the day of hCG trigger and ICSI outcome. Method: This was a retrospective, non-interventional, observational, cohort study of patients undergoing ICSI at 21st Century Group of Hospitals, Killa Pardi and Surat, Gujarat during the period of January 2018 to March 2018. Patients with age group of 20-40 years who underwent ICSI-ET using GnRH antagonist flexible protocol during this period, had obtained 2 or more MII oocytes during retrieval and had at least one grade I embryo transferred were included in this study. Women using donor oocytes were excluded. Serum progesterone levels were analysed on day of hCG trigger. Total 165 patients were included in the study. They were divided into two groups, those with β-hCG less than or equal to 1.5 ng/ml and those with β-hCG more than 1.5 ng/ml. Student’s t test and Chi square test were used to compare the clinical pregnancy rates between two groups. Results: Clinical pregnancy rate decreases with increase in serum progesterone levels on the day of hCG trigger. Patients with serum progesterone levels ≤1.5 ng/ml had significantly higher clinical pregnancy rates than those with progesterone levels >1.5 ng/ml (45% vs 6%; p :<0.001). Conclusion: Pre-hCG rise in serum Progesterone concentration does not affect the oocyte quality. But, it significantly decreases the chances of implantation and the clinical pregnancy rates.